Liver Fat in the Metabolic Syndrome - Kotronen, Anna; Westerbacka, Jukka; Bergholm, Robert; Pietiläinen, Kirsi H.; Yki-Järvinen, Hannele (The journal of clinical endocrinology and metabolism, 2007)
Background: The liver, once fatty, overproduces components of the metabolic syndrome, such as glucose and lipids. The amount of liver fat in subjects with and without the metabolic syndrome has not been determined. It is unknown which clinically available markers best reflect liver fat content. Measurements: Components of the metabolic syndrome as defined by the International Diabetes Federation and liver fat content by proton magnetic resonance spectroscopy were measured in 271 nondiabetic subjects (162 women, 109 men). In addition, other features of insulin resistance (serum insulin, C-peptide), intraabdominal and sc fat by magnetic resonance imaging, and liver enzymes (serum alanine aminotransferase and serum aspartate aminotransferase) were measured. Results: Liver fat was 4-fold higher in subjects with [n = 116; median 8.2% (interquartile range 3.2–18.7%)] than without [n = 155; 2.0% (1.0–5.0%); P < 0.0001] the metabolic syndrome. This increase in liver fat remained significant after adjusting for age, gender, and body mass index. All components of the metabolic syndrome correlated with liver fat content. The best correlate was waist in both women (r = 0.59, P < 0.0001) and men (r = 0.56, P < 0.0001). Liver fat correlated significantly with serum alanine aminotransferase (r = 0.39, P < 0.0001 for women; r = 0.44, P < 0.0001 for men) and aspartate aminotransferase (r = 0.27, P = 0.0005 for women; r = 0.31, P = 0.0012 for men) concentrations. The best correlates of liver fat were fasting serum insulin (r = 0.61; P < 0.0001 for both women and men) and C-peptide (r = 0.62; P < 0.0001 for both women and men). Conclusions: Liver fat content is significantly increased in subjects with the metabolic syndrome as compared with those without the syndrome, independently of age, gender, and body mass index. Of other markers, serum C-peptide is the strongest correlate of liver fat.